Experimental and Analytical Investigation on the Corner Failure in Masonry Buildings: Interaction between Rocking-Sliding and Horizontal Flexure. Issue 2 (7th February 2020) - Casapulla, Claudia; Maione, Alessandra
ABSTRACT: The failure mechanism of corners in masonry buildings has frequently been observed in seismic scenarios, but only a few works and no experimental investigations devoted to it are available in the literature. In this aritcle, the experimental behavior of a simple masonry corner is first analyzed, by simulating the seismic horizontal actions through a progressive tilting of the supporting base. Then, the conditions of the onset of two possible failure modes are analytically formulated: they are the rocking-sliding and the horizontal flexure mechanism. A three-dimensional macro-block model with frictional joints is used to analyze these mechanisms, while the crack patterns and the load factors are derived through the kinematic approach of the limit analysis. The evaluation of the in-plane frictional resistances involved by the rocking-sliding mechanism is performed by applying a reliable criterion previously proposed, while for the torsion strength involved in the horizontal flexure mechanism, simplified yield conditions are adopted and a possible criterion is also introduced to take into account the actual reduction of the contact surfaces. Last, the experimental findings are compared and critically interpreted in light of the analytical results and the influence of the main parameters on the prevailing mechanism is highlighted.